Gerakan Pendidikan al-Washliyah di Sumatera Utara - Dja’far Siddik; Rosnita Rosnita (Universitas Islam Negeri Mataram, 2014)
In the context of Islamic organization in Indonesia, researchers tend to focus their study on the well-known Muslim organizations, such as NU and Muhammadiyah; they tend to overlook other Islamic movements, such as Al-Jam’iyatul Washliyah in Northern Sumatera. This article examines Al-Washilah’s history and role, especially in education that covers its educational institutions, types, and problems. It argues that Al-Washliyah is very committed to the dynamics of Islamic education in the country, and plays a role as a stronghold for the Sunni tradition. Al-Washilah has contributed to the formation of Islamic culture in Malay world (Nusantara) since the colonial era and is concerned with broader issues, ranging from politics, culture, propagation, economy to education. Al-Washliyah has long played an important role for the continuity of the tradition of Islam in Indonesia.